Association between leukotriene receptor antagonist therapy and Churg-Strauss syndrome: an analysis of the FDA AERS database. Issue 2 (10th February 2010) - Bibby, S; Healy, B; Steele, R; Kumareswaran, K; Nelson, H; Beasley, R
Abstract : Background: The possible role of leukotriene receptor antagonist (LTRA) therapy in the pathogenesis of Churg-Strauss syndrome (CSS) is uncertain. The aim was to examine the association between LTRA therapy and CSS in cases registered in the FDA Adverse Event Reporting System (AERS) database. Methods: All cases of suspected drug-induced CSS reported to the AERS database between November 1997 and April 2003 were reviewed. Subjects in whom LTRAs were the suspected medication and sufficient documentation existed to confirm the diagnosis of CSS were sequentially categorised into one of the following groups: (A) CSS before treatment initiation; (B) oral or inhaled corticosteroids reduced or stopped within 6 months of CSS onset; (C) possible prodromal phase of CSS at treatment initiation; (D) unstable asthma at treatment initiation; (E) stable asthma at treatment initiation. Results: There were 181 case reports of suspected drug-induced CSS with sufficient documentation to confirm a diagnosis of CSS; in 163 (90%) an LTRA was a suspect medication. In 140 of these 163 cases there was sufficient documentation to sequentially categorise the case into groups, with 13 (9%) in A, 27 (19%) in B, 11 (8%) in C, 28 (20%) in D and 61 (44%) in E. Conclusion: LTRA therapy was a suspect medication in most confirmed cases of CSS reported in the AERS database. In the majority of cases treated with an LTRA, CSS could not be explained by either corticosteroid withdrawal or pre-existing CSS. These findings are informative in considering the potential associations between LTRA therapy and CSS.